Helminto e artropodofauna de Paroaria coronata (Miller, 1776) (Passeriformes: Emberzidae) - Mascarenhas, Carolina Silveira (2008)
Paroaria coronata (red-crested cardinal) occurs only of South America. The species is not in danger of extinction, but it is appreciated by the illegal trade in wild animals. His parasite fauna is little known and has been recorded only one Nematoda and three Phthiraptera. The diet is mainly based greasses seeds, but can consume small fruit and insects. The study aimed to identify helminths and arthropods associated with red-crested cardinal and for that were examined wild birds, captives and of undetermined origin, totaling 40 specimes. The wild birds and undetermined origin were the most parasitized. The helminthfauna was composed of Aproctella carinii, Dispharynx nasuta, Capillaria sp. Diplotriaena sp. (Nematoda); Tanaisia oviaspera, Tanaisia valida, Tanaisia sp., Prosthogonimus ovatus (Trematoda); Orthoskrjabinia sp. (Cestoda); Mediorhynchus sp. (Acanthocephala). Tanaisia sp. was most prevalent (10%) and more abundant (0.48), D. nasuta and Orthoskrjabinia sp. occurred with greater mean intensity of parasitism (5 helminths/host). The arthropodfauna was represented by Myrsidea coronatae, Philopterus sp. and Brueelia sp. (Phthiraptera); Ptilonyssus sairae and Sternostoma pirangae (Gamasida), where M. coronatae and P. sairae were the most prevalent with 65% and 50%, respectively. All helminths are reported for the first time in P. coronata, Orthoskrjabinia sp. is recorded for the first time in Brazil; A. carinii, Diplotriaena sp., T. valida, T. oviaspera and Mediorhynchus sp. are cited for the first time in the Rio Grande do Sul state. The helminthfauna found in P. coronata, indicates that the species is omnivorous eating habits. Among the arthropods, Philopterus sp., Brueelia sp., P. sairae and S. pirangae have your first record infecting P. coronata; M. coronatae is recorded for the first time in Brazil, this report marks the first occurrence of S. pirangae in Brazil and the first of P. sairae in the Rio Grande do Sul state.